Prevalence and correlates of latent tuberculosis infection among employees of a high security prison in Malaysia. - Al-Darraji, Haider Abdulrazzaq Abed; Tan, Cynthia; Kamarulzaman, Adeeba; Altice, Frederick L (Occupational and environmental medicine, 2015)
Although prison employees share the same tuberculosis (TB) risk environment with prisoners, the magnitude of TB problems among prison employees is unknown in most resource-limited prisons. This survey was conducted to investigate the prevalence and correlates of tuberculin skin test (TST) positivity among employees in Malaysia's largest prison.